CryoEM structure and Alphafold molecular modelling of a novel molluscan hemocyanin - Gaia Pasqualetto; Andrew Mack; Emily Lewis; Ryan Cooper; Alistair Holland; Ufuk Borucu; Judith Mantell; Tom Davies; Miriam Weckener; Dan Clare; Tom Green; Pete Kille; et al. (PLoS ONE, 2023)
Hemocyanins are multimeric oxygen transport proteins present in the blood of arthropods and molluscs, containing up to 8 oxygen-binding functional units per monomer. In molluscs, hemocyanins are assembled in decamer ‘building blocks’ formed of 5 dimer ‘plates’, routinely forming didecamer or higher-order assemblies with d5 or c5 symmetry. Here we describe the cryoEM structures of the didecamer (20-mer) and tridecamer (30-mer) forms of a novel hemocyanin from the slipper limpet Crepidula fornicata (SLH) at 7.0 and 4.7 Å resolution respectively. We show that two decamers assemble in a ‘tail-tail’ configuration, forming a partially capped cylinder, with an additional decamer adding on in ‘head-tail’ configuration to make the tridecamer. Analysis of SLH samples shows substantial heterogeneity, suggesting the presence of many higher-order multimers including tetra- and pentadecamers, formed by successive addition of decamers in head-tail configuration. Retrieval of sequence data for a full-length isoform of SLH enabled the use of Alphafold to produce a molecular model of SLH, which indicated the formation of dimer slabs with high similarity to those found in keyhole limpet hemocyanin. The fit of the molecular model to the cryoEM density was excellent, showing an overall structure where the final two functional units of the subunit (FU-g and FU-h) form the partial cap at one end of the decamer, and permitting analysis of the subunit interfaces governing the assembly of tail-tail and head-tail decamer interactions as well as potential sites for N-glycosylation. Our work contributes to the understanding of higher-order oligomer formation in molluscan hemocyanins and demonstrates the utility of Alphafold for building accurate structural models of large oligomeric proteins.